Implementasi Model Pembelajaran Picture and Picture dan Ceramah Pada Mata Pelajaran IPAS Peserta Didik Fase C SDN 097349 Mayang Tahun Pelajaran 2024 / 2025 - Hutauruk, Hotdiana; Arent, Ease; Saragih, Hisarma; Napitu, Ulung (LPPM Institut Pendidikan Nusantara Global, 2025)
In the context of Indonesian education, challenges rooted in geographic diversity, demographic spread, and cultural plurality significantly influence the quality and accessibility of learning. The implementation of effective teaching models is crucial, especially in primary education, where student engagement and comprehension are essential. This study aims to explore the implementation of two contrasting instructional models picture and picture and the lecture method in IPAS (Social and Natural Sciences) learning for Phase C students at SDN 097349 Mayang during the 2024/2025 academic year. A qualitative descriptive research design with a case study approach was employed. Data were collected through observations and interviews involving two teachers and ten students, and were analyzed descriptively. The findings revealed that the Picture and Picture model, which incorporates visual media to enhance student comprehension and engagement, significantly improved participation and concept mastery among students. In contrast, the lecture method, though structured and time-efficient, resulted in lower student interaction and reduced learning outcomes. The results highlight that integrating visual-based and interactive methods into the learning process can enhance student motivation and understanding. The study recommends the synergistic application of both models to create a more adaptive and holistic instructional approach suited to the contextual needs of primary school students.